2008
DOI: 10.1074/jbc.m710332200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Yeast SM22 Homologue Scp1 and Actin Demonstrate the Importance of Actin Bundling in Endocytosis

Abstract: The yeast SM22 homologue Scp1 has previously been shown to act as an actin-bundling protein in vitro. In cells, Scp1 localizes to the cortical actin patches that form as part of the invagination process during endocytosis, and its function overlaps with that of the well characterized yeast fimbrin homologue Sac6p. In this work we have used live cell imaging to demonstrate the importance of key residues in the Scp1 actin interface. We have defined two actin binding domains within Scp1 that allow the protein to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 31 publications
5
40
0
12
Order By: Relevance
“…This is short compared with many other endocytic proteins such as Sla1 (~25-30 seconds and Abp1 ~15-18 seconds), but more similar to timing of Myo3 and Myo5 (~10-12 seconds), the actin-binding protein Sac6 (10-12 seconds) and the amphiphysins (~ 9-10 seconds) (Gheorghe et al, 2008;Jonsdottir and Li, 2004;Kaksonen et al, 2003;Kaksonen et al, 2005). Timing of its arrival at the membrane, about 5 seconds after Abp1, indicate that it is not 3503 Yeast dynamin Vps1 functions in endocytosis functioning in recruitment of endocytic coat or early acting F-actin polymerisation factors and most likely has a role at the onset or during the invagination step of endocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is short compared with many other endocytic proteins such as Sla1 (~25-30 seconds and Abp1 ~15-18 seconds), but more similar to timing of Myo3 and Myo5 (~10-12 seconds), the actin-binding protein Sac6 (10-12 seconds) and the amphiphysins (~ 9-10 seconds) (Gheorghe et al, 2008;Jonsdottir and Li, 2004;Kaksonen et al, 2003;Kaksonen et al, 2005). Timing of its arrival at the membrane, about 5 seconds after Abp1, indicate that it is not 3503 Yeast dynamin Vps1 functions in endocytosis functioning in recruitment of endocytic coat or early acting F-actin polymerisation factors and most likely has a role at the onset or during the invagination step of endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have indicated no internalisation defects in cells lacking vps1 expression (Geli and Riezman, 1998), others have demonstrated effects of vps1 deletion on uptake of uracil permease (Fur4) activity (Yu and Cai, 2004). Deletion of many genes encoding proteins with accepted roles in endocytosis, such as Cap1, Scp1, Abp1, are reported to have no defect in several assays (Gheorghe et al, 2008;Huang et al, 1999;Kaksonen et al, 2005;Maldonado-Baez et al, 2008). However, the assays are often performed on fixed cells or over long time courses that do not detect more subtle, kinetic changes in uptake.…”
Section: Deletion Of Vps1 Confers Defects On Endocytic Machinerymentioning
confidence: 99%
“…Alternatively, differences in surface charge distribution between LdACT and RbACT may be responsible for the bundling property of LdACT filaments. Actin bundling has recently been shown to play an important role in endocytosis (62). Interestingly, depletion of actin in the bloodstream form of T. brucei focused its role during endocytosis, which is an indispensable process for the survival of the parasites (6).…”
Section: Discussionmentioning
confidence: 99%
“…However, since this earlier study, more sensitive assays have been developed using live cell imaging and the analysis of the kinetic behavior of proteins involved in endocytosis (Kaksonen et al, 2003). Many proteins previously observed to have no endocytic phenotype are now considered core proteins in the process; these proteins include capping protein and the bundling proteins Abp1 and Scp1 (Kaksonen et al, 2005;Gheorghe et al, 2008). Three proteins were analyzed in the presence and absence of ysc84.…”
Section: Function Of Ysc84 In Endocytosismentioning
confidence: 99%
“…However, once activated it is thought that Las17 binds to and activates Arp2/3 that in turn initiates actin polymerization at the site (Winter et al, 1999;Rodal et al, 2005). The formation of branched and bundled actin structures at the patch have been shown to be critical for the invagination process (Galletta et al, 2008;Gheorghe et al, 2008). It is proposed that a strong actin framework allows force to be generated against this structure to allow the plasma membrane to be directed into the cell.…”
Section: Introductionmentioning
confidence: 99%